Effects of Cu on microstructure and some properties of as-drawn Zn-2Al alloys. (22nd March 2019) - Wu, Qilong; Li, Yujia; Liu, Shengxin; Long, Weimin; Chen, Yong
Abstract: The microstructure and some properties of as-drawn Zn-2Al alloys with different content of Cu were investigated by SEM, EDS, XRD and DSC techniques. The results showed that the main phases of Zn-2Al alloys free of Cu were η and α phases. However, the distribution of η and α phases was uneven. The microstructure of Zn-2Al alloys adding Cu became more uniform than those of Zn-2Al alloys and the ε phase (CuZn4) appeared in the alloys containing Cu not less than 2.0 wt%. The content of eutectic component decreased while Cu was added to Zn-2Al alloys. The hardness raised with the increasing of Cu content (0 ∼ 3.0 wt%), while the bending number decreased. It was worthy noting that adding Cu obviously influenced on the corrosion resistance of the Zn-2Al alloys.